Linux Virtual Server Setup - Earnpin Lee; Yee Loon Lee; Wan Ching Lee (Penerbit UTHM, 2004)
In this book, you will find practical guide to setup a server with Red Hat operating system. The server is configured to support virtual services by hosting multiple domains in a single machine. It covers the installation and configuration of various services including web server, FTP server, SMTP/POP3 email, SQL server and etc. This book features expanded information on system administration, console tools and other resources that is applicable to real-world environment. Often used commands and system check list are included.